The impact of new glucose monitoring systems on parameters of diabetes metabolic control. Literature review - Salasa, Weronika; Seredyński, Tomasz; Mądry, Wojciech; Mazurkiewicz, Aleksandra; Kołodziej, Magdalena; Męczyńska, Joanna; Saiuk, Nazarii; Kozicz, Michał Andrzej; Wojciechowska, Adriana; Marcicka, Justyna (Journal of Education, Health and Sport, 2024)
Introduction In recent years, there has been tremendous development in medicine, including diabetology. A significant portion of these achievements pertains to pharmacological treatment. However, one should not overlook the advancement of devices necessary for monitoring glucose levels, such as glucometers or CGM and FGM systems. In this paper, I want to focus on how the use of glucose monitoring systems affects the course of diabetes. Aim of the study The aim of this study was to determine the impact of glucose monitoring systems (CGM and FGM) on parameters of metabolic control in diabetes. Materials and methods The article was created based on the PubMed and Scholar databases. The literature was analyzed using the following keywords: Continuous glucose monitor, CGM, flash glucose monitoring, FGM, type 1 diabetes, type 2 diabetes, diabetes mellitus, Metrics of Glycemic. Results Research has confirmed that the use of continuous glucose monitoring systems lowers HbA1c in patients with both type 1 and type 2 diabetes regardless of age and treatment modality. Furthermore, the use of CGM and FGM reduces the number of hypoglycemic episodes and increases time in range (TIR). Conclusions Thanks to the results obtained from numerous studies, it can be assumed that the use of continuous glucose monitoring systems is not only an adjunct to diabetes therapy but also an important component of it. With this technology combined with modern medications, we can achieve better glycemic control and, consequently, improve the quality of life of patients with diabetes.